The International Mycological Association: its history in brief with summaries of its International Mycological Congresses and diverse international relationships - E.G. Simmons (IMA Fungus)
This history presents a review of International Mycological Association activities, its international congresses, and its relationships with regional mycological associations as well as with international organizations of other scientific disciplines. The IMA was organized in 1971 during the First Mycological Congress (IMC-1) convened at Exeter, U.K. In the period 1971 to 2010, nine international congresses have been held, each with its own organizational structure but under the guidance of one of the successive inter-Congress management groups of IMA officers and executive committee members. The congress list includes Exeter, U.K.; Tampa, U.S.A.; Tokyo, Japan; Regensburg, Germany; Vancouver, Canada; Jerusalem, Israel; Oslo, Norway; Cairns, Australia; and Edinburgh, Scotland. Inter-congress activities of each IMA executive group are summarized. The characteristics of each congress are surveyed as to organization, programming, attendance numbers, finances, and satellite meetings.The IMA has sponsored the establishment of Regional Mycological Associations beginning in 1977 and has lent operational funding. Regional associations currently are functional and hold their own regional congresses in Africa, Asia, Australasia, Europe, and Latin America. The relationships of the IMA with other organizations recognized within the supra-national International Council of Scientific Unions are discussed.